Kvinnorollerna i antikens teater - skrivna, spelade och sedda av män - Hov , Live (Tidskrift för genusvetenskap, 1997)
The theatre of the Antiquity constitutes the first chapter in our common western history of t h e theatr e and should therefore be a well-known as well as an important subject for anyone interested in t h e a t r e research. This article gives a short presentation of this field of research not primarily geared at experts b u t r a t h e r at interested general readers. Why do we n e e d to increase our knowledge on the roles of women in antique theatre? As I see it, this knowledge is i m p o r t a n t on two d i f f e r e n t levels. On one level, it is exciting and rewarding in itself to delve d e e p e r i n t o a past, where women’s roles and women’s lives both resemble and differ f r om our own. On a different, a n d more professional level, it is i m p o r t a n t to g am insight into how women’s roles evolved in order to see how the image of women was construed inside the theatre. II I have paid more attention to the Roman drama than to the Greek it is because, in my opinion, the f o r m e r has had a greater impact on women’s roles in years to come - in world drama as a whole. The Greek tragedy has b e e n an inexhaustible source of inspiration for world drama and it’s always had the highest status a n d that goes for the female tragic roles too. But it is t h e stereotyped women of Roman comedy that are easily recognisable everywhere in western drama, today as well as in earlier repertoire. Women have been cast as meddlesome mothers, p e r t maid servants or attractive young things. They have had few functions outside the private sphere, whereas the male parts have to a greater extent been individualised and have portrayed men in a variety of occupations and positions, thereby m i r r o r i n g the limited choice of g e n d e r roles for women in the outside world.